KONSEP PERLINDUNGAN HUKUM TERHADAP MASYARAKAT SEBAGAI KORBAN PENCEMARAN LINGKUNGAN AKIBAT PEMBAKARAN LAHAN PADA SAAT PANEN DI LAMPUNG TENGAH - Hermawati Hermawati; Yeni widowaty (Universitas Janabadra, 2018)
Sugarcane burning activities carried out by the company have been included in the category of environmental pollution as stipulated in the Environmental Law mentioned above. This is indicated by the entry or inclusion of substances, energy, and / or other components into the environment by human activities, so that the quality of the environment becomes down to a certain level which causes the environment to not function properly. The smoke caused by the burning is very disturbing, both directly / indirectly can pollute and / or damage the living environment of the surrounding residents. The purpose of this study was to find out, describe, and analyze how the implementation of legal protection for people as victims of burning land at the time of sugarcane harvest in Central Lampung and to formulate the concept of future legal protection for the community as victims of land burning at sugarcane harvest in Lampung Middle. This type of research used is empirical juridical. Research results The implementation of legal protection for communities as victims of environmental pollution due to the burning of sugarcane land at the time of harvest in Central Lampung did not work properly because there was no legal protection and compensation at all for the community around the sugar cane plantation. improve legislation that is considered to have weaknesses or does not fulfill the sense of justice of the community. To create a new law, to be able to replace the legislation that is considered to have many weaknesses or not to fulfill the sense of justice of the community.Keywords: Legal Protection, Environmental Pollution, Victims